Effect of the Porous Texture of Activated Carbons on the Electrochemical Properties of Molecule-Grafted Carbon Products in Organic Media. Issue 12 (5th September 2015) - Lebègue, Estelle; Benoit, Corentin; Brousse, Thierry; Gaubicher, Joël; Cougnon, Charles
Abstract : Two commercial activated carbons, different from their texture, were grafted with electroactive molecules and tested for determining what texture is well-suited for the grafting. Microporous and mesoporous carbons, having approximately the same BET surface area, were selected. The electroactive molecule consists in a naphthalimide compound having an amine as surface attachment group. The present work was divided in two parts. In a first part, the modified carbons were characterized by thermal gravimetric analysis, X-ray photoelectron spectroscopy, elemental chemical analysis and nitrogen gas adsorption measurements have been used for studying the impact of the grafting on the textural properties of carbons. In a second part, the electrochemical properties of the modified carbons were studied in propylene carbonate +1 M Bu4 NBF4 . Results show that the grafting ruins the performances of the microporous carbon, while the mesoporous carbon appears well-suited for the grafting, showing a good compromise between electrolyte-accessibility and ionic transportation.